Serum Apelin Peptide Level in Hemodialysis Patients With Pulmonary Arterial Hypertension (Iranian Journal of Kidney Diseases, 2018)
Introduction. Pulmonary arterial hypertension (PAH) is a destructive disease that is characterized by vasoconstriction, alterations and abnormal angiogenesis in pulmonary vessels, and right ventricular dysfunction. There is no certain treatment known for this condition. Patients with PAH have a lower level of apelin in their blood and less apelin is secreted in their endothelial cells, but this condition is not investigated in hemodialysis patients. This study aimed to compare apelin level in hemodialysis patients with and without PAH. Materials and Methods. Forty hemodialysis patients with PAH were compared with 40 patients without the condition. Apelin serum level was measured using an enzyme-linked immunosorbent assay technique. Dialysis adequacy was measured and its relationship with apelin level and the pulmonary arterial pressure was investigated. Results. The mean level of apelin in the group suffering from PAH was 54.87 ± 23.50 ng/L, while it was 76.85 ± 34.66 ng/L in those without PAH (P = .001). It was also found that hemodialysis adequacy had no effect on apelin level or pulmonary arterial pressure. Conclusion. The findings of our study suggest that in hemodialysis patients with PAH, apelin peptide serum levels are significantly lower than patients with normal arterial pressure and this condition is not affected by hemodialysis.